2015
DOI: 10.1002/etc.2937
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite stress variably stimulates pro‐oxidant enzymes, anatomical deformities, photosynthetic pigment reduction, and antioxidants in arsenic‐tolerant and sensitive rice seedlings

Abstract: Contamination of arsenic (As) in rice (Oryza sativa L.) paddies and subsequent uptake by rice plants is a serious concern, because rice is a staple crop for millions of people. Identification of As toxicity and detoxification mechanisms in paddy rice cultivars would help to reduce As-associated risk. Arsenic tolerance and susceptibility mechanisms were investigated in 2 differential As-accumulating rice genotypes, Triguna and IET-4786, selected from initial screening of 52 rice cultivars as an As-tolerant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…This observation is in keeping with the MANOVA results ( Table 1 and Supplementary Table S1 ). One possible biological interpretation is that Arsenic toxicity, mainly in the form of oxidative stress, determined a chain of physiological and biochemical changes within ripening tomato fruit to produce a network of oxidizing/reducing mechanisms more complex than that observed in roots and shoots ( Tripathi et al, 2015 ; Pandey et al, 2016 ). In this context the alleviation of As-induced stress effected by Si was less clear cut than in roots and shoots ( Romero-Aranda et al, 2006 ; Gunes et al, 2007 ; Cao et al, 2015 ) and more effective on the long term.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in keeping with the MANOVA results ( Table 1 and Supplementary Table S1 ). One possible biological interpretation is that Arsenic toxicity, mainly in the form of oxidative stress, determined a chain of physiological and biochemical changes within ripening tomato fruit to produce a network of oxidizing/reducing mechanisms more complex than that observed in roots and shoots ( Tripathi et al, 2015 ; Pandey et al, 2016 ). In this context the alleviation of As-induced stress effected by Si was less clear cut than in roots and shoots ( Romero-Aranda et al, 2006 ; Gunes et al, 2007 ; Cao et al, 2015 ) and more effective on the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Tripathi et al . () reported that a tolerant rice cultivar produced more antioxidants, such as proline, dehydroascorbate and glutathione peroxidase, whereas these declined in a sensitive cultivar, resulting in greater susceptibility to arsenic. Apart from acting as an osmolyte, proline contributes to stabilising subcellular structures, scavenging free radicals and buffering cellular redox potential under stress conditions (Ashraf & Foolad ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that arsenic‐contaminated soil has a harmful effect on plant growth through perturbation of numerous metabolic pathways and other biological functions and antimony‐contaminated soil induces similar adverse effects on growth . Strikingly, plants exposed to either inorganic arsenic or antimony respond by increasing their intracellular proline content . In leishmania, no changes in expression of G5K, glutamate‐5‐semi‐aldehyde dehydrogenase or pyrroline‐5‐carboxylate reductase have been noted in whole‐genome sequencing, proteomics or gene expression studies comparing drug‐sensitive and drug‐resistant parasites .…”
Section: Discussionmentioning
confidence: 99%